Философские идеи Фридриха Ницше - Прокопец, В. А. (ХНУРЕ, 2020)
In this work, the activity of the great German philosopher of science Friedrich Wilhelm Nietzsche was analyzed, who became famous for his ideas, which became one of the masterpieces of non-classical philosophy of the 19th century.His image of the superman has been and remains one of the most unique interesting and contradictory philosophical theses to this day, and his critical approach to understanding the prevailing dogmas, ideals and morals will cause interest among the modern reader and readers of future generations.
Keywords: философия; философские идеи Фридриха Ницше